Factors predicting delirium among hospitalized older adults in an urban area, Thailand: A prospective cohort study - Duangrat Kaveenuntachai; Naphatthorn Prueksaanantakal; Pirunnapa Benyapad; Pratin Chinpinkleaw; Sirichai Jiojinda (Belitung Nursing Journal)
Background: Delirium is a common but often underrecognized complication in hospitalized older adults. It is associated with poor outcomes, including longer hospital stays, increased mortality, and long-term cognitive decline. While numerous studies have explored factors contributing to delirium, there is a lack of research on the context of older adults in Bangkok, Thailand. Understanding the predictors of delirium is crucial for early detection and prevention, particularly in an urban hospital setting.